Some Thoughts on Urban Living Trends 2022 - Anna Sungkar (Dekonstruksi, 2023)
The pandemic has accelerated urban people to conduct transactions, commerce, business and online movement. However, before and outside the pandemic, there is a trend towards increasing religiosity, the hijab as a fashion trend, the coffee craze, the corporatization of warteg, the tendency to shop via smartphones, a fondness for antiques, and a sluggishness in contemporary art, which should be noted. There is the L-project, an art project that tries to break free from the frozen art commerce.